Communication from the executive of the Commonwealth, transmitting the nomination of Richard Thomas Zarvona, as Colonel of volunteers (LLMC-digital (Series), 1861)
Governor John Letcher's July 1, 1861 letter of nomination of Richard T. Zarvona to Colonel of Volunteers.